The preventive direction of modern theories of health and health-saving in public health and education - Shevchenko, A. S.; Shevchenko, V. V.; Brown G.W., G. W. (Харківський національний медичний університет, 2024)
Background. The modern understanding of health is related to the need to prevent diseases caused by infections, lifestyle, environmental and genetic factors. Ukrainian legislation guarantees health care, but the practice of implementing laws is imperfect. The teaching of valeological disciplines in educational institutions is of great importance for the prevention of diseases. But the content of these disciplines requires constant revision from the point of view of evidencebased medicine, and the creation of new preventive programs requires theoretical justification. Aim. To determine the content and practical significance of the modern understanding of health care in public health care and education. Materials and Methods. Methods of bibliosemantic and system analysis were used. Results. The theory of health and health-saving is considered using cross-cultural, discursive, norm-centric, phenomenological, holistic, axiological and integral approaches, from the perspective of evidence-based and "4P" medicine. Health-saving is shown as derived from a healthy lifestyle and valeological competence formed in the population. The best environment for the formation of a healthy lifestyle is shown to be an educational environment, the tools of formation are valeological disciplines and education of medical and social non-government organizations. The need for joint efforts of the population and medical workers to achieve better results in the prevention of socially significant diseases is determined. Conclusions. Improvement of the preventive direction of valeological education is closely related to the competence approach, in particular, with the formation of valeological competence. The public health system should use the potential of educational valeological programs to form a healthy lifestyle in new generations during their studies at higher education institutions. For the formation of high-quality valeological programs, a permanent partnership of educators and medical professionals is necessary.
Keywords: valeological competence; evidence-based medicine; 4P medicine; Health Pedagogy